Predictive molecular markers in metastases to the central nervous system: recent advances and future avenues - Bergmeister-Berghoff, Anna Sophie; Deimling, Andreas von (Acta neuropathologica, 2014)
Metastases to the central nervous system (CNS) are common in several cancer types. For most primary tumors that commonly metastasize to the CNS, molecular biomarker analyses are recommended in the clinical setting for selection of appropriate targeted therapies. Therapeutic efficacy of some of these agents has been documented in patients with brain metastases, and molecular testing of CNS metastases should be considered in the clinical setting. Here, we summarize the clinically relevant biomarker tests that should be considered in neurosurgical specimens based on the current recommendations of the European Society of Medical Oncology (ESMO) or the National Comprehensive Cancer Network (NCCN) for the most relevant primary tumor types: lung cancer (EGFR mutations, ALK rearrangement, BRAF mutations), breast cancer (HER2 amplification, steroid receptor overexpression), melanoma (BRAF mutations), and colorectal cancer (RAS mutations). Furthermore, we discuss emerging therapeutic targets including novel oncogenic alterations (ROS1 rearrangements, FGFR1 amplifications, CMET amplifications, and others) and molecular features of the tumor microenvironment (including immune-checkpoint molecules such as CTLA4 and PD-1/PD-L1). We also discuss the potential role of advanced biomarker tests such as next-generation sequencing and “liquid biopsies” for patients with CNS metastases.